2020
DOI: 10.1108/bfj-03-2020-0280
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contamination in processed seafood and the associated health risk for Malaysian women

Abstract: PurposeMalaysians are the highest seafood consumers in the region; be it fresh or processed. Environmental pollution has put the safety of seafood at stake, heavy metals among others. This study was done to assess the health risk associated with selected heavy metals ingestion from processed seafood.Design/methodology/approachThe most preferred processed seafood type and the intake rates were determined from a cross-sectional survey among communities in Shah Alam, Selangor (n = 90). The processed seafood were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In addition, a previous study revealed that a high ratio of Se/Hg in fish was related to low bioaccessibility of MeHg according to the in vitro method [ 46 ]. Other potentially toxic elements reported as usually contaminating fish and other seafood products are cadmium, arsenic, and lead, which are harmful to humans [ 47 ]. Long-term consumption of foods that are contaminated with these elements can increase the risk of cancer development [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study revealed that a high ratio of Se/Hg in fish was related to low bioaccessibility of MeHg according to the in vitro method [ 46 ]. Other potentially toxic elements reported as usually contaminating fish and other seafood products are cadmium, arsenic, and lead, which are harmful to humans [ 47 ]. Long-term consumption of foods that are contaminated with these elements can increase the risk of cancer development [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data on Se:Hg molar ratio in fish was reported at 0.23–1 [ 40 , 41 ]. Other heavy metals that could contaminate aquatic animals, such as Cadmium (Cd), Arsenic (As), and Lead (Pb) [ 42 ], are well known as harmful to the human body and have been reported to elevate the risk of cancer development [ 43 ]. Hence, future studies are needed to determine heavy metals concentrations in commonly consumed fish in Thailand to ensure that the amounts of contaminated elements are below the maximum levels for fish and seafood according to the criteria of FAO (i.e., Pb < 0.3 mg/kg, Hg < 1.2–1.6 mg/kg, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Diet is a primary source of heavy metal to humans contributing to more than 90% of exposure 24,59 . Considering that ubiquitous exposure to heavy metal exposure is a significant threat to women health, 60,61 bio-monitoring of hair heavy metal analysis have been proposed for routine clinical screening and diagnosis 62 . Hair heavy metals is an indicator reflecting elements from diet than environmental exposure.…”
Section: Discussionmentioning
confidence: 99%